Model free active flow control of a simplified car model. Issue 5 (2019) - Plumejeau, B.; Delprat, S.; Keirsbulck, L.
Abstract: A model free control (MFC) approach is presented and used to symmetrize the unstable wake flow of a simplified car model named Ahmed body. Such unstable phenomena with regards to the space-time evolution of the low pressure wake vortex core, is known to increase the global drag of square back vehicles. Results highlight the ability of a MFC to reduce the wake symmetry breaking phenomena by using lateral blowing slit jets. A model free control scheme derived from (Fliess and Join, 2013) is proposed and a tuning procedure is suggested. At last experimental results on an Ahmed body in wind tunnel are provided.